2004
DOI: 10.3348/kjr.2004.5.2.107
|View full text |Cite
|
Sign up to set email alerts
|

Bronchiolitis Obliterans after Allogenic Bone Marrow Transplantation: HRCT Findings

Abstract: ObjectiveTo evaluate the high resolution computed tomography (HRCT) findings of bronchiolitis obliterans (BO) after bone marrow transplantation (BMT).Materials and MethodsDuring the past three years, 11 patients were diagnosed as having BO after BMT when they developed irreversible air flow obstruction, with an FEV1 value of less than 80% of the baseline value, without any clinical evidence of infection. All 11 patients underwent HRCT, of whom eight also underwent follow-up HRCT. The HRCT images were assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 30 publications
1
17
2
Order By: Relevance
“…4 Moreover, although the accuracy of lung HRCT for the diagnosis of BO post SCT has not been precisely evaluated, air trapping was always present in these patients in two small series. 10,11 Different radiological scores have been proposed for the quantification of air trapping on expiratory slices. 18,[20][21][22] However, limitations to these scoring systems exist, mainly due to sensitivity and specificity for disease progression and Table 3 Evolution of dyspnea evaluated by NYHA Classification at last follow-up…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Moreover, although the accuracy of lung HRCT for the diagnosis of BO post SCT has not been precisely evaluated, air trapping was always present in these patients in two small series. 10,11 Different radiological scores have been proposed for the quantification of air trapping on expiratory slices. 18,[20][21][22] However, limitations to these scoring systems exist, mainly due to sensitivity and specificity for disease progression and Table 3 Evolution of dyspnea evaluated by NYHA Classification at last follow-up…”
Section: Discussionmentioning
confidence: 99%
“…9 Available lung HRCT in small series of patients with post-SCT BO showed air trapping at full expiration in all cases, strongly suggesting that lung HRCT should be considered for diagnosis of this disease. 10,11 Furthermore, lung HRCT may allow identification of patients at an earlier stage of BO, before the development of a significant airflow obstruction on pulmonary function tests.…”
Section: Introductionmentioning
confidence: 99%
“…12 These criteria were modified to include the following five criteria: (1) airway obstruction7hypoxaemia not normalizing after b-2 agonist treatment, [13][14][15] (2) absence of pulmonary infiltrates, (3) absence of infectious organisms in blood and respiratory secretion7bronchoal-veolar lavage, (4) reduction in FEV 1 in the absence of airway restriction (in patients cooperating in pulmonary function measurements), 14,15 (5) bronchial dilatation and mosaic pattern of attenuation on high-resolution CT scan. [16][17][18] Patients fulfilling at least four of five criteria were diagnosed as BO and treated with high-dose pulse corticosteroid therapy (methylprednisolone 10 mg/kg body weight/day) for 3 days. Courses of pulse therapy were repeated on a monthly basis in patients with continuous symptoms up to a maximum of six cycles.…”
Section: Methodsmentioning
confidence: 99%
“…High-resolution computed tomography (HRCT) of the chest is much more sensitive in detecting signs of BO and is the radiological procedure of choice in evaluating these patients [40][41][42]. While the study may still be normal in the early stages of BO, it usually shows signs of hyperinflation with areas of decreased attenuation.…”
Section: Radiological Evaluationmentioning
confidence: 99%
“…Some studies demonstrated that the presence of expiratory air trapping preceded the PFT criteria for BO [44]. In a study of 11 patients with BO following HSCT who underwent HRCT of the chest, all were found to have abnormal findings, and all patients had progression of radiological findings over time [41]. The most common finding was decreased lung attention, especially in the lower lobes, and expiratory air trapping (n511).…”
Section: Radiological Evaluationmentioning
confidence: 99%